PENGARUH KEPEMIMPINAN DAN KEPADUAN TIM TERHADAP KEEFEKTIFAN TIM KERJA PPPPTK MEDAN - Anom, Siti; Sinaga, Sarman (LPPM Universitas Darma Agung, 2020)
In connection with the improvement of services Center of Development and Empowerment for Teachers and Education Personnel (PPPPTK) Medan, the empowerment of teamwork in the institution becomes very important because the success of the teamwork will determine the overall success of the institution. The purpose of the study was to determine whether team leadership, and team cohesion have direct impact on team effectiveness at Center of Development and Empowerment for Teachers and Education Personnel (PPPPTK) Medan. The population are all trainers and staff at Center of Development and Empowerment for Teachers and Education Personnel Medan with number 187 people. Sampling technique used is proportional stratified random sampling, so sampling size is 127. Data were processed used path analysis. The results of study showed: First, team cohesion is directly influenced by team leadership with level of effect is 0,30. Second, team effectivenessis directly influenced by team leadership with level of effect is 0,20 and indirect effect is 0,14. Third, team effectiveness is directly influenced by team cohesion with level of effect is 0,29. From the finding, it can be recommended: (1) giving training to all staff, trainer and team leader in P4TK for understanding about teamwork and improve their interpersonal competence to be good team player, (2) supporting every unit/teamwork with resources they needed to accomplish work, (3) giving reward for the most effective and cohesive team, (4) doing teambuilding correctly and regularly.